The comparative value of corn and whole and ground milo as swine-fattening feeds. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
Sorghum grains are grown extensively in parts of Kansas for hog feed. In previous feeding test with hogs at this station, some sorghum grains have given excellent results compared with corn. In 1950 Westland and Midland milos gave 12 percent greater daily gain than corn. The economy in feed per 100 pounds gain was about 5 percent better from sorghum grain than from corn. Because corn has been more difficult to produce in Kansas, while sorghum grains have increased in popularity, it was thought advisable to compare sorghum grain with corn again. Four lots of pigs were self-fed in dry lot. All lots received a mixed animal and plant protein supplement of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal. The milo was an unidentified variety, straight elevator run. Lot 1 received shelled corn; Lot 2, whole milo; Lot 3, coarsely ground milo from a burr mill; Lot 4, ground milo. The protein supplement mixture for this lot contained aureomycin supplied as Aurofac at the rate of 27 pounds per ton.
Keywords: Swine; Corn; Whole milo; Ground milo; Aureomycin; Gain